The Symbolic Stage of Desire: An Exploration of Lacan's Theory in The Context of We Need To Talk About Kevin - Kristiawan, Vino (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
Nowadays, a lot of mental problems arise in an individual, especially a child. This is due to the trauma felt by the individual. The most common case is the disharmonious relationship between parents and children. In fact, the family is one of the first educators or character builders before an individual knows the outside world. Through the discussion of the symbolic system that influences the emergence of desire in the We Need to Talk About Kevin movie chest released in 2011 by Lynne Ramsay, it shows how the symbolic stage influences the mental formation and interaction of individuals with others. By doing a careful reading of the subtitles and analyzing the film, this research aims to prove the influence of the symbolic stage in shaping individual characters. It is evidenced by the formation of a psychopathic personality in the main character due to the harsh treatment of his parents. The influence on his relationship with others is evident in the lack of quality interaction shown by the character. Symbolic stage also affects the character's mental health. It is characterized as manipulative, two-sided, and antisocial or alienated from the outside world. Indicating that it traumatizes the individual.  Keywords: Symbolic, Desire, Relationship, Mental Health, Psychopaths